Social Control Among Female Kindergarten Students (Journal of the College of Basic Education, 2024)
The current research aims to identify social control among female students in the kindergarten department. The research sample consisted of (400) female students, who were selected by a stratified random method with an appropriate distribution from the College of Basic Education, Kindergarten Department, Al-Mustansiriya University. The social control scale by (Al-Shehabi 2018), which the researcher adopted. The scale in its final form consists of (81) items distributed over (3) areas, namely (family, college, customs and traditions). The researcher verified the psychometric properties of the scale from its apparent validity by presenting the attitudes On (15) experts, construct validity using the two extreme groups method (discriminatory power), the correlation of the item score with the total score of the scale, the correlation of the areas of social control with each other, and checking the reliability using the (Facronbach) method, so the calculated reliability coefficient reached (87.0).After applying the tool to the research sample and analyzing the data, the researcher concluded that the female students of the kindergarten department were distinguished by social control. In light of the research results, the researcher came up with a set of recommendations for holding educational seminars to shed light on proactive decisions as a basis for performing tasks efficiently. They aim to solve problems before they occur. Establishing extracurricular activities aimed at developing social control among university students, through participation, cooperation, and building positive social friendships